Space and Socialityu in a Lundayeh Community Kampung Kaban Long House in Sipitang, Sabah - Riong, Adam; Aminuddin, Asrul (MAJ - Malaysia Architectural Journal, 2020)
This study expand our understanding of longhouses within the context of a minority Lundayeh ethnic. Longhouse is a co-housing concept housing typology that often can be found within the indigenous communities in Borneo. A housing concept where a collective of families made a pact to built and stay as a community in the form of a longhouse. The architecture of a Longhouse are commonly known with the shared public long corridor that goes along the longitudinal of the Longhouse, where communial activities are often being conducted by the communities. Each families will each have separated entrance to each private housing quarters. Each quarters are unique due to personalisation and economical capability by each family. But sadly Longhouse housing typology are getting less in number in the process of urbanization. This research will conduct a qualitative research that aim to explore the impact of a Longhouse architecture to the space and sociality on a Lundayeh Community in Sipitang Sabah. Allowing us to understand better of the values that made Longhouse to be successful in creating a rich community culture and social well being compared to the modern housing. This exploration hope to inspire better translation and definition of a housing scheme that not only satisfy the economical needs but also the culture and social needs in our daily life.